FRI0481 No Change in Self-Reported Pain from Pre-Pregnancy To Six Months Postpartum in Women with Juvenile Idiopathic Arthritis. (15th July 2016) - Jakobsen, B.; Koksvik, H.S.; Ursin, K.; Wallenius, M.
Abstract : Background: There are no previous studies on health related quality of life (HRQL) related to pregnancy in women with juvenile idiopathic arthritis (JIA). One study on a small population with rheumatoid arthritis (RA) using the short form 36 (SF-36) to measure HRQL, has shown that RA women reported a worsening in the aspect of bodily pain 12 and 24 weeks postpartum compared to pre-pregnancy (1). Objectives: To study the impact of pregnancy on the aspect of bodily pain aspect in self- reported HRQL using SF-36 from pre-pregnancy to six months postpartum on women with JIA. Methods: 25 women with JIA were followed from pre-pregnancy to six months postpartum. HRQL was measured using the SF-36 form resulting in eight multi-item subscales. In this study the aspect of bodily pain in SF-36 was explored. Registrations were recorded pre-pregnancy (within one year before conception), 1st trimester (1–12 weeks), 2nd trimester (13–27 weeks), 3rd trimester (28–40 weeks), six weeks and six months postpartum. The Wilcoxon test for related samples was performed. Results: Mean age of the JIA women was 29 years (range 20–36) and mean disease duration 21 years (range 4–32). The mean number of DMARDs used before pregnancy was 0.64 (range 0–2). Correspondingly, the mean number of DMARDs were 0.68 (range 0–1) six months postpartum. The pre-pregnancy scores were tested to each of the other time points. There was a statistically significantly improvement in self-reported pain from pre-pregnancy to six weeks postpartum (p=0.019), but no difference was observed at six months postpartum. Conclusions: There was a no statistically significant change in self-reported pain from pre-pregnancy to six months postpartum, but a significantly improvement was seen from pre-pregnancy to six weeks postpartum in this study population of JIA women. References: Förger F, Østensen M, Schumacher A, et al. Impact of pregnancy on health related quality of life evaluated prospectively in pregnant women with rheumatic diseases by the SF-36 health survey. Annals of the rheumatic diseases 2005; 64: 1494–9. Disclosure of Interest: None declared